THE STRUCTURE OF THE SYNAXARION AKC. 2706, KEPT IN THE NATIONAL LIBRARY OF POLAND: SEPTEMBER–NOVEMBER - CHISTIAKOVA, MARINA (Knygotyra, 2010)
The Synaxarion, a spiritual calendar collection, was translated from Greek no later than the late 12th century. First used in liturgy, it was supplemented with pastoral texts in the 1160s, and evolved into something close to an encyclopedia for the Orthodox. The Synaxarion contains short lives of the saints, teachings, stories, and explanations of church holidays, written by eminent Byzantian and Slavonic apologists and arranged from September 1st to August 31st. This extremely popular collection served as a stimulant for Christian education in the Slavonic countries.The research project focuses on the end of 16th – beginning of 17th century synaxarion Akc. 2706 (texts for the period of September to February), kept in the National Library of Poland. The manuscript was discovered at the Poland-Ukraine border, in the library of the Peremyshl Uniate Chapter, and was part of the collection of bishop Jan Snigurski (1784–1847).The synaxarion reveals a creative rearrangement of the calendar collection of lives of the saints and teachings, implemented by the bookmen of the Grand Duchy of Lithuania. The objective of the paper was to conduct an analysis of the peculiar aspects of the contents and language of the copy Akc. 2706 that would lead to an understanding of the main principles of how the sources were dealt with. In order to ensure a thorough research approach, the analysis of the structural innovations in this type of Synaxarion was based on the comparative, source analysis, and textological methods. The theses on the composition and language of the copy Akc. 2706 are illustrated with examples from the texts for the three autumn months. The main outcome of the research is as follows: the National Library of Poland copy of the autumn period, Akc. 2706, belongs to the unique undocumented second type of the Plain Synaxarion. The initiators of this type were the Orthodox bookmen of the GDL, who renewed and rearranged the contents of the Synaxarion.The arrangement of the Akc. 2706 copy or its protograph was based on the second edition of the Plain Synaxarion. The readings of this edition were used in order, but in slightly smaller numbers. Although a continuation of an earlier tradition is evident, the research shows the section including lives and teachings of the saints to contain certain innovations. The contents of the copy Akc. 2706 underwent substantial changes: first, a different calendar order was used in arranging the readings of the second edition of the yearly Synaxarion; second, additional sources were used, mainly from chronicles and other reading collections. The text has been randomly checked against Synaxarion copies of other structural types. Comparative analysis reveals a connection with the GDL tradition of synaxarian editions and textological groups, represented by the following copies: Wróblewski Library of the Lithuanian Academy of Sciences, f-19, nos. 95, 96; S. Uvarov‘s collection, Moscow State Historical Museum, 56-1°; National Library of Belarus 091/4218 К; Library of the Catholic University of Lublin, no. 198, etc. In the structure of the Akc. 2706 copy the texts of these sources are contaminated.Knowing these peculiarities of the contents of the Akc. 2706 copy will enable book researchers, manuscript historians, and textologists to trace other copies to the GDL Orthodox tradition. The recreation of the peculiar aspects of spiritual manuscript collections – an important part of the GDL written heritage – will be facilitated by the structuring of these data.
Keywords: ...